1998
DOI: 10.1021/om970886o
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Reactivity of β-Diketiminato Aluminum Complexes

Abstract: The preparation and reaction chemistry of β-diketiminato aluminum complexes are described. (TTP)AlCl2 (1) (TTPH = 2-(p-tolylamino)-4-(p-tolylimino)-2-pentene) is formed by the treatment of AlCl3 with LiTTP. Sequential alkylation of 1 with CH3Li results in the formation of the mono- and dimethyl aluminum complexes (TTP)AlMeCl (2) and (TTP)AlMe2 (3), respectively. Only monoalkyl complexes are produced when more hindered alkyllithium reagents are used. Compounds 2 and 3 are more conveniently prepared by treating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
165
2
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(196 citation statements)
references
References 29 publications
24
165
2
1
Order By: Relevance
“…11 A 55 survey of the published data revealed that a straightforward metathetical reaction between the lithiated ligand 1 and group 13 halides fails to proceed beyond 1:1 stoichiometry. 12 Taking into account the scarcity of published works on spirocyclic complexes of the NacNac ligand with group 13 60 elements, we turned our attention to computational pre-screening of 3-6 in order to determine the best possible candidates for synthesis (Electronic Supporting Information, ESI). Geometry optimizations and subsequent frequency analyses carried out using density functional theory (DFT) revealed that the majority 65 of the investigated systems are stable minima on the potential energy hypersurface, thereby confirming their viability as synthetic targets.…”
mentioning
confidence: 99%
“…11 A 55 survey of the published data revealed that a straightforward metathetical reaction between the lithiated ligand 1 and group 13 halides fails to proceed beyond 1:1 stoichiometry. 12 Taking into account the scarcity of published works on spirocyclic complexes of the NacNac ligand with group 13 60 elements, we turned our attention to computational pre-screening of 3-6 in order to determine the best possible candidates for synthesis (Electronic Supporting Information, ESI). Geometry optimizations and subsequent frequency analyses carried out using density functional theory (DFT) revealed that the majority 65 of the investigated systems are stable minima on the potential energy hypersurface, thereby confirming their viability as synthetic targets.…”
mentioning
confidence: 99%
“…The zinccarbon bond lengths average to 1.978 and the average aluminum-methyl bond lengths (Al À C 1.972 , Al À C 1.9675 ) are comparable to those reported for [LAlMe 2 ] (Al À C1 1.955(4) , Al À C2 1.961(3) ). [12] Complex 5 is soluble in various aromatic and polar solvents. …”
Section: Resultsmentioning
confidence: 99%
“…The 1 H NMR spectrum exhibited a triplet at δ = 0.05 ppm (J HF = 1.4 Hz) characteristic of an Al-Me resonance coupled to the α-fluorines of a coordinated C 6 F 5 group. [17] The resonances of the phim fragment were generally shifted downfield with respect to the relative resonances of the precursor 1. Two quintets in the same 1 H NMR spectrum at 1.33 and 0.96 ppm indicated the presence of MeB(C 6 F 5 ) 2 and Me 2 B(C 6 F 5 ) in a 4:1 molar ratio.…”
Section: Reactivity Studies: Reactions Between Al Complexes 1 and 2 Amentioning
confidence: 95%
“…Treatment of dialkylaluminium complexes bearing bidentate N,N-or N,O-ligands with B(C 6 F 5 ) 3 leads to unstable tricoordinate alkylaluminium cations, which react quite rapidly by abstracting a C 6 F 5 group from the MeB-(C 6 F 5 ) 3 -anion to form neutral LnAlR(C 6 F 5 ) products. [17] Several studies have shown that the presence of a Lewis base (L 1 ) can stabilise the aluminium cation through the formation of {LX}Al(R)(L 1 ) + adducts. [18] Gibson et al showed that a pendant donor group that in the neutral aluminium complexes is weakly bonding or nonbonding becomes a normal donor group in the cationic derivatives upon treatment with B(C 6 F 5 ) 3 , thus stabilising these species.…”
Section: Reactivity Studies: Reactions Between Al Complexes 1 and 2 Amentioning
confidence: 99%